2022
DOI: 10.1002/cam4.5475
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram based on the lymph node metastasis indicators for patients with bladder cancer: A SEER population‐based study and external validation

Abstract: Purpose This study aimed to compare the prognostic value of multiple lymph node metastasis (LNM) indicators and to develop optimal prognostic nomograms for bladder cancer (BC) patients. Methods BC patients were obtained from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015, and randomly partitioned into training and internal validation cohorts. Genomic and clinical data were collected from The Cancer Genome Atlas (TCGA) as external v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In other words, the prognosis of patients with 1 positive lymph node out of 1 harvested lymph node is of vital difference from patients with 20 positive lymph nodes out of 20 harvested lymph nodes, which casts doubt on the predictive value of LNR, a metric extensively studied in non-colorectal malignancies, including breast cancer, esophageal cancer, non-small cell lung cancer, and oropharyngeal cancer [ 17 20 ], but failing to further stratify patients with 0 or 1 PLN [ 21 ]. Meanwhile, LODDS, a novel LNM-related indicator for predicting cancer prognosis, has been put forward in previous studies where suggesting LODDS outperforms other LN status indicators in predicting the prognosis of bladder cancer, rectal cancer, small cell lung cancer, and so forth [ 22 24 ]. Since the presence of LNM is related to poor prognosis and determines the need for adjuvant therapy [ 25 , 26 ], it is imperative to identify independent LN prognostic factors for SRCC and incorporate the indicators with the best predictive performances in an effort to construct a nomogram for SRCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the prognosis of patients with 1 positive lymph node out of 1 harvested lymph node is of vital difference from patients with 20 positive lymph nodes out of 20 harvested lymph nodes, which casts doubt on the predictive value of LNR, a metric extensively studied in non-colorectal malignancies, including breast cancer, esophageal cancer, non-small cell lung cancer, and oropharyngeal cancer [ 17 20 ], but failing to further stratify patients with 0 or 1 PLN [ 21 ]. Meanwhile, LODDS, a novel LNM-related indicator for predicting cancer prognosis, has been put forward in previous studies where suggesting LODDS outperforms other LN status indicators in predicting the prognosis of bladder cancer, rectal cancer, small cell lung cancer, and so forth [ 22 24 ]. Since the presence of LNM is related to poor prognosis and determines the need for adjuvant therapy [ 25 , 26 ], it is imperative to identify independent LN prognostic factors for SRCC and incorporate the indicators with the best predictive performances in an effort to construct a nomogram for SRCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. compared the predictive efficiency of LNM indexes by constructing a multifactorial Cox regression model, and found that LODDS was superior to N classification, PLN and LNR in prognosticating OS and CSS in prostate cancer patients ( 28 ); Zhao et al. compared the effectiveness of N classification, PLN, LNR and LODDS in predicting cancer-specific survival in patients with small cell lung cancer and found that the LODDS model showed the highest accuracy in predicting cancer-specific survival in patients with small cell lung cancer compared to N classification, PLN and LNR ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no studies have investigated common and distinct prognostic factors for liver, lung, bone, and brain metastasis in extensive-stage SCLC (ES-SCLC) patients. Nomograms, which integrate various predictors to provide comprehensive survival outcomes, have found widespread application in evaluating patient prognosis across different cancer types (Hu et al 2022 ; Li et al 2022 ). However, only two studies have so far involved constructing nomograms for the prognosis of ES-SCLC patients with metastasis, and the predictive performance of these models remains to be improved (Shan et al 2021 ; Fan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%